2006
DOI: 10.1080/03610920600579929
|View full text |Cite
|
Sign up to set email alerts
|

Bivariate Sign Test for One-Sample Bivariate Location Model Using Ranked Set Sample

Abstract: In this article, we introduce a bivariate sign test for the one-sample bivariate location model using a bivariate ranked set sample (BVRSS). We show that the proposed test is asymptotically more efficient than its counterpart sign test based on a bivariate simple random sample (BVSRS). The asymptotic null distribution and the non centrality parameter are derived. The asymptotic distribution of the vector of sample median as an estimator of the locations of the bivariate model is introduced. Theoretical and num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Larocque et al 10 introduced an affine-invariant modification of the Wilcoxon signed-rank test for bivariate location problems. The advantage of this test over Jan and Randles 11 test is that its asymptotic null distribution holds without assuming elliptical symmetry. Samawi 12 introduced a bivariate sign test for the one-sample bivariate location problem using a bivariate ranked set sample.…”
Section: Introductionmentioning
confidence: 99%
“…Larocque et al 10 introduced an affine-invariant modification of the Wilcoxon signed-rank test for bivariate location problems. The advantage of this test over Jan and Randles 11 test is that its asymptotic null distribution holds without assuming elliptical symmetry. Samawi 12 introduced a bivariate sign test for the one-sample bivariate location problem using a bivariate ranked set sample.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to Hettmansperger [11] and Samawi et al [30], based on Le Cam's third lemma [10, page 208], we derive the limiting distribution of (1/ √ nS T along a sequence of alternatives, θ n = θ / √ n, converging to 0 when using ABVRSS. Note that E θ…”
Section: Asymptotic Relative Pitman Efficiencymentioning
confidence: 92%
“…Note that Samawi et al's [30] BVRSS sign test is just a special case when J s = J (J ABVRSS ) . In this paper, we consider only the symmetric AVRSS designs which provide that E(S T ) = 0.…”
Section: Sign Test Using An Alternative Bvrssmentioning
confidence: 97%
See 1 more Smart Citation
“…Other authors have used the RSS sampling method to improve parametric and nonparametric statistical inference. For nonparametric methods, RSS was considered by [12][13][14][15] and [16]. Koti and Babu [17] showed that the RSS sign test it provides is a more powerful test than the SRS sign test.…”
Section: Introductionmentioning
confidence: 99%